Gum and Resin Production and Marketing: Implications for Pastoral Livelihood in Adadle District, Somali Region, Ethiopia - Bishar Ahmed Yussuf; Latamo Lameso Lelamo; Mahamud Mahamed Abdi (International Journal of Forestry Research)
Both locally and nationally, Ethiopia’s gum resin sector has a substantial economic impact. Even though collecting and selling gum and resin is one of the main livelihood activities in Ethiopia’s remote pastoral areas, there are few case studies that adequately reflect national realities. Therefore, the goal of this study is to pinpoint and evaluate gum and resin production and sale, as well as any implications for pastoral livelihood, in the Adadle district of the Somali Region. Both purposive and random sampling techniques were employed. The primary data gathering technique used were household surveys, key informant interviews, focus groups, market surveys, direct observation, and surveys of community-based organizations. Multiple response tests, one-way ANOVA, and descriptive statistics were used in SPSS Version 26 to statistically analyze the collected data. The study discovered many Acacia, Boswellia, and Commiphora tree species that are employed in the production of gum and resin. It was also found that natural oozing and artificial tapping were the methods used for collecting and harvesting gum and resin. The average amount of gum and resin/frankincense harvested annually by each family was 219.82 kg and 58.27 kg, respectively, with gum harvesting being substantially higher (p 0.05) than resin harvesting. The recurrent drought, season, and awareness level of harvesters on taping were the factors affecting the quantity and quality of production. The average annual household income from gum and resin/frankincense was 18,684 Ethiopian Birr and 43,704 Ethiopian Birr, respectively. The mean annual income from resin was substantially larger (p 0.05) than that of gum. The gum and resin market chain in the area comprises eight actors with five market channels. The research also demonstrates that the income made by selling gum and resin was used to pay for basic necessities for the family, save money for health care and medications, and pay for social concerns and educational expenses. Recurrent drought, lack of market access and market expertise, lack of institutional cooperatives, and lack of infrastructure and facilities were all determined to be obstacles to the production and sale of gum and resin. Generally, resources should be conserved and interventions should be done to ensure the sustainability of the resource base and improve production potential. Proper tapping techniques should be introduced to enhance production potential, and access to market information should be ensured to maximize primary producers’ income share insured for maximizing the income share of primary producers.